MICE GERBILS IN MODERN EXPERIMENTS - Pohil, S.I.; Toryanik, I.; Timchenko, A.N.; Chigirinskaya, N.A.; Kostyrya, I. (World of Medicine and Biology, 2015)
The presented paper is devoted to the study of experimental use of mice gerbils (mice family, Muridae; subspecies - gerbils, Gerbillinae) in Medical Parasitology. The work contains a brief historical data on the use of experimental animals in research, programs, projects, and their trends, analysis of the results, possible prospects. Specialists are given prerogatives and advantages of mice use in the laboratory (70% of the total number of experimental animals in the world of science is given to mice). The authors have shown a generalized information concerning methods of content gerbils in captivity, breeding, fattening of specificity, habits, some aspects of animal psychology and their inherent natural socialization.
Keywords: mouse gerbil; experiment; medical parasitology; history; selection; content zoopsychology